Effect of ply thickness on tensile and bending performances of carbon fiber reinforced thermoplastic unidirectional laminate. Issue 3 (29th December 2022) - Liu, Haolin; Ma, Xinqi; Jiang, Lin; Sang, Lin; Hou, Wenbin; Zhang, Zhuqing; Wu, Haihong
Abstract: It has been explored that thin ply would improve the mechanical performances of carbon fiber reinforced epoxy composites laminate. It has not been known whether there are similar effects on thermoplastic composites. In this article, carbon fiber reinforced polyamide 6 (CF/PA6) unidirectional fabrics with two thicknesses of 0.045 and 0.105 mm were used to fabricate the unidirectional laminate (UDL). Tensile and bending behaviors of the UDL were recorded with a digital image correlation (DIC) system, their damage macro‐morphologies were observed with high‐speed camera during loading. The fracture microstructures of the samples were observed with SEM and optic microscope. The results showed that the tensile and bending strengths of the samples with 0.045 mm thick are 79.8% and 24.8% higher than that with 0.105 mm thick. Thinning ply can inhibit the crack expanding, and the time from crack originating to fracture of the sample is larger than that of the thick ply one. Morphologies of the fractures revealed that the crack mainly expanded in the matrix along the loading direction for thin‐ply laminate, while the crack developed in the fiber cluster for thick‐ply laminate. The results also revealed that the mechanical properties of the laminate can be improved obviously by using thin‐ply.